Effective treatment of bronchopleural fistula with empyema by pedicled latissimus dorsi muscle flap transfer: Two case report. Issue 41 (9th October 2020) - He, Zhongliang; Shen, Lifeng; Xu, Weihua; He, Xiaowen
Abstract: Rationale: Bronchopleural fistula (BPF) is a dreaded complication after lobectomy or pneumonectomy and is associated with high morbidity and mortality. Successful management remains challenging when this condition is combined with empyema, and the initial treatment is usually conservative and endoscopic, but operative intervention may be required in refractory cases. Patient concerns: Two patients diagnosed with BPF with empyema were selected to undergo surgery in our hospital because they could not be cured by conservative and endoscopic therapy for 1 or more years. One was a 70-year-old man who had a 1-year history of fever and cough after he received a minimally invasive right lower lobectomy for intermediate lung adenocarcinoma and chemotherapy 2 years ago; the other was a 73-year-old man who had a 2-year history of cough and fever after he underwent a minimally invasive right upper lobectomy for early lung adenocarcinoma 3 years earlier. Diagnosis: Both patients were diagnosed with BPF with empyema. Interventions: After receiving conservative and endoscopic therapies, both patients underwent pedicled latissimus dorsi muscle flap transfers for complete filling of the empyema cavity. Outcomes: The patients recovered very well, with no recurrence of BPF and empyema during postoperative follow-up. Lessons: It is crucial to not only completely control infection and occlude BPFs, but also obliterate the empyema cavity. Thus, pedicled latissimus dorsi muscle flap transfer associated with conservative and endoscopic therapies for BPF with empyema is a useful treatment option, offering feasible and efficient management with promising results.